Infants' and toddlers' physical activity and sedentary time as measured by accelerometry: a systematic review and meta-analysis - Brianne A. Bruijns; Stephanie Truelove; Andrew M. Johnson; Jason Gilliland; Patricia Tucker (BMC, 2020)
Abstract Background Early experiences in physical activity (PA) are important to shape healthy movement behaviours long-term; as such, it is critical that PA is promoted from infancy, and that detrimental behaviours (e.g., prolonged sedentary time [ST]) are minimized. The purpose of this systematic review and meta-analysis was to examine infants' and toddlers' movement behaviours across daytime hours. Methods Seven online databases were searched for terms related to infants (< 12 months), toddlers (12-35.9 months), PA, ST, and accelerometry. Two independent reviewers examined 4873 articles for peer-reviewed original research, published in English, that assessed infants' (counts/min) and/or toddlers' PA or ST (min/day) using accelerometry across daytime hours. Infants' mean PA level (counts/min) was averaged across studies, and ranges were produced. Estimates of toddlers' movement behaviours were aggregated meta-analytically to produce average daily rates, and accelerometer placement, cut-point validity, device type, and epoch length were tested as a moderating variables. Results Twenty-four studies from 16 countries (published 2011-2019), representing 3699 participants, were included in the systematic review. Five studies reported on infants' PA, which ranged from 78.2 to 2580.5 cpm. Across 20 studies, toddlers' total PA, light PA, moderate-to vigorous-intensity PA, and ST ranged from 72.9 to 636.5, 48.5 to 582.4, 6.5 to 89.9, and 172.7 to 545.0 min/day, respectively. After taking into account accelerometer placement, cut-point validity, device type, and epoch length, we found that toddlers engaged in 246.19 min/day (SE = 28.50; 95% CI: 190.34, 302.04) of total PA, 194.10 min/day (SE = 28.76; 95% CI: 137.73, 250.47) of light PA, and 60.16 min/day (SE = 5.88; 95% CI: 48.64, 71.69) of moderate-to vigorous-intensity PA. Toddlers engaged in 337.04 min/day (SE = 32.67; 95% CI: 273.01, 401.07) of ST. Conclusions With limited studies conducted in infants (n = 5), PA estimates are inconclusive and largely heterogeneous. Overall, toddlers tend to exceed the total PA recommendation of 180 min/day; however, very little of this time is spent at higher movement intensities. Even with high PA rates, toddlers still engage in substantial ST. More consistent and valid measurement protocols are needed to improve comparability across studies.